2016
DOI: 10.5539/mas.v11n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of MLP and RBF Neural Networks to Estimate the Soil Saturated Hydraulic Conductivity

Abstract: Soil saturated hydraulic conductivity is considered one of the physical soil properties that is very important in modeling of water movement and environmental studies. This study aimed to compare the performance of Multi-Layer Perceptron (MLP) and Radial Basis Function (RBF) in neural networks for estimation of the soil saturated hydraulic conductivity. For this, the data of 27 drilled cased borehole permeameter with three kinds of geometry water flow through the soils and the soil texture properties were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In accordance with our results, Moosavi et al [ 24 ] in soils of Fars Province, Iran, stated the capability of different approaches to predict sorptivity coefficient could be ranked as MLPNNs > RBFNNs > MLR regarding their accuracies and computational times. Furthermore, Shams Emamzadeh et al [ 91 ] in soils of Tehran Province, Iran, found MLPNNs predicted K 0 was more accurate than that of RBFNNs. While, Rezaei Arshad et al [ 36 ], reported more capability of RBFNNs to predict K 0 compared to MLPNNs and MLR methods in soils of Khuzestan Province, Iran.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our results, Moosavi et al [ 24 ] in soils of Fars Province, Iran, stated the capability of different approaches to predict sorptivity coefficient could be ranked as MLPNNs > RBFNNs > MLR regarding their accuracies and computational times. Furthermore, Shams Emamzadeh et al [ 91 ] in soils of Tehran Province, Iran, found MLPNNs predicted K 0 was more accurate than that of RBFNNs. While, Rezaei Arshad et al [ 36 ], reported more capability of RBFNNs to predict K 0 compared to MLPNNs and MLR methods in soils of Khuzestan Province, Iran.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the RBF in the present study is in agreement with the results of Gao and Liu (2010), who successfully applied the RBF network method for the prediction of the SWRC. Many researchers have applied the RBF method to predict the SWRC (Achieng, 2019;Bayat et al, 2011;Bayat, Neyshaburi, Mohammadi, Nariman-Zadeh, Irannejad, & Gregory, 2013), soil saturated hydraulic conductivity (Emamzadeh et al, 2016), specific surface area (Bayat, Ersahin, & Hepper, 2013) and soil cation exchange capacity (CEC; Ghorbani et al, 2015). Also, Alavi et al (2009) utilized the RBF method for predicting proctor parameters.…”
Section: Discussionmentioning
confidence: 99%